Table-top Coherent Diffractive Imaging using a Fiber Laser Driven High-order Harmonic Source - Eschen, Wilhelm; Tadesse, Getnet K.; Klas, Robert; Hilbert, Vinzenz; Tuitje, Frederik; Steinert, Michael; Schelle, Detlef; Nathanael, Anne; Schrempel, Frank; Schuster, Vittoria; Zürch, Michael; Pertsch, Thomas; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
Laser development in the recent years has pushed the coherent XUV flux of high-harmonic generation to values that are comparable to synchrotrons1. This development enables Coherent Diffractive Imaging experiments on a lab scale that were before only possible at large scale facilities. In this contribution we present our latest results on table-top lensless XUV-Imaging. Achieving record-high resolutions using a high-order harmonic source at 18 nm with two different imaging modalities. Using the Fourier Transform Holography (FTH) method a record resolution of 23 nm was demonstrated. With the more general ptychographic method we were able to resolve features down to a size of 45 nm. Further, we show our recent advances towards imaging at the technological relevant wavelength of 13.5 nm.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Coherent Diffractive Imaging; Fiber Laser; Fourier Transform Holography; High-order Harmonic Generation; Ptychography